2021
DOI: 10.1093/cercor/bhab269
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Activation of Interneuron Subtypes Modulates Visual Contrast Responses of Mouse V1 Neurons

Abstract: Interneurons are critical for information processing in the cortex. In vitro optogenetic studies in mouse primary visual cortex (V1) have sketched the connectivity of a local neural circuit comprising excitatory pyramidal neurons and distinct interneuron subtypes that express parvalbumin (Pvalb+), somatostatin (SOM+), or vasoactive intestinal peptide (VIP+). However, in vivo studies focusing on V1 orientation tuning have ascribed discrepant computational roles to specific interneuron subtypes. Here, we sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
17
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 80 publications
7
17
3
Order By: Relevance
“…These two modes of lateral inhibition provide flexible ways to control behavioral sensitivity to visual contrast spanning extensive retinotopic space (∼70° in our experiments). On the other hand, driving either SST or PV neurons directly at the retinotopic site of visual input (where both SST and PV connections to excitatory neurons are dense) invariably caused divisive effects on perceptual responses, consistent with prior studies of local inhibition on contrast perception 57 and neural selectivity 25,28,58,59 . Although some studies have shown that local SST inhibition preceding visual input can cause subtractive effects on V1 firing rates 27,60 , divisive effects on firing rates dominate when visual excitation and local SST inhibition overlap in time 25,26 , as was the case here.…”
Section: Discussionsupporting
confidence: 82%
“…These two modes of lateral inhibition provide flexible ways to control behavioral sensitivity to visual contrast spanning extensive retinotopic space (∼70° in our experiments). On the other hand, driving either SST or PV neurons directly at the retinotopic site of visual input (where both SST and PV connections to excitatory neurons are dense) invariably caused divisive effects on perceptual responses, consistent with prior studies of local inhibition on contrast perception 57 and neural selectivity 25,28,58,59 . Although some studies have shown that local SST inhibition preceding visual input can cause subtractive effects on V1 firing rates 27,60 , divisive effects on firing rates dominate when visual excitation and local SST inhibition overlap in time 25,26 , as was the case here.…”
Section: Discussionsupporting
confidence: 82%
“…Within a central cylinder with a radius of 50 µm, i.e. within spike detection range of a vertically penetrating extracellular electrode (Henze et al, 2000;Buzsáki, 2004), we found 15 PCs and 13 PV+ interneurons with robust tuning, which is roughly comparable to the average number of tuned cells per mouse of 8.2 PCs and 3.0 PV+ neurons respectively in Shapiro et al (2022). Unlike the original study we found no Sst+ neurons with robust tuning.…”
Section: Contrast Tuning Modulation By Optogenetic Activation Of Inte...supporting
confidence: 51%
“…Mirroring the analyses of Shapiro et al (2022), we first identified a population of neurons based on their contrast tuning. Specifically, we considered neurons with robust, monotonically increasing tuning behavior (see Supp.…”
Section: Contrast Tuning Modulation By Optogenetic Activation Of Inte...mentioning
confidence: 99%
“…Better studied, however, is the immediate effect of increasing activity in VIP interneurons, which leads to enhanced firing of local pyramidal cells 23,28 . This effect has been observed across many regions of sensory 20,21,[29][30][31][32][33][34] , motor 35 and prefrontal cortex 36,37 .…”
Section: Introductionmentioning
confidence: 89%
“…Better studied, however, is the immediate effect of increasing activity in VIP interneurons, which leads to enhanced firing of local pyramidal cells 23,27 . This effect has been observed across many regions of sensory 20,21,[28][29][30][31][32][33] , motor 34 and prefrontal cortex 35,36 . Disinhibitory modulation of sensory cortex through VIP and SOM interneurons has in fact been proposed to be the core mechanism underlying attentional modulation in visual cortex 37,38 .…”
mentioning
confidence: 87%